Palliative sedation in covid19: Knowledge and attitudes - Riveros Ríos, Miriam Elisa (2021)
The Covid19 Pandemic can generate challenges and difficulties for decision-making, especially in patients with advanced, incurable diseases with limited life prognosis. For this reason, palliative care should be developed with ethical, scientific and human criteria with the basic tool of assertive communication that will reduce the suffering of patients, families and health personnel.The objective of this work is to determine knowledge and attitudes about the care of patients at the end of life in Pandemic Covid19 and palliative sedation.The descriptive study was used as methodology, cross-sectional study by anonymous survey of health professionals from various healthcare centers.160 professionals were surveyed,Ages between 25 and 71 years old, 68% women, 68.8% doctors, 12.5% nurses, 15.6% kinesiologist, Years of practice in the profession 43.2 % over 20 years, Knowledge: 90.6% triage criteria, 81.9% criteria for admission to ICU, 51.9% criteria for not admission to ICU, 79.4% basic management of dyspnea, 26.3 % management of refractory dyspnea, 60% criteria for termination of a disease, 55.6% palliative sedation, 26.5% drug for palliative sedation, attitudes; 38.1% would not administer palliative sedation to a terminally ill patient suffering from refractory dyspnea, 25% are not sure if palliative sedation is euthanasia, 3.7% affirm palliative sedation is euthanasia.Knowledge was identified 79.4% basic management of dyspnea, 26.3% management of refractory dyspnea, 55.6% palliative sedation, only 26.5% which drugs are used, Attitude; 38.1% part would not use palliative sedation and 25% are not sure it is euthanasia.